Benchmarking Food and Beverage Companies on Obesity Prevention and Nutrition Policies: Evaluation of the BIA-Obesity Australia Initiative, 2017-2019 - Ella Robinson; Miranda R. Blake; Gary Sacks (Kerman University of Medical Sciences, 2021)
BackgroundThe potential role of the food and beverage industry in addressing diet-related disease is much debated, particularly amidst evidence of the targeted strategies, including voluntary self-regulation, used by the industry to influence policy in their favour. At the same time, the need for more comprehensive action to address unhealthy diets has led to a focus on increasing the accountability of different stakeholders. However, there has been limited evaluation of the impact of accountability initiatives on food and beverage company policies and practices. This study evaluated the impact of the BIA-Obesity (Business Impact Assessment - Obesity and population nutrition) Australia Initiative that benchmarked major Australian food and beverage companies on their nutrition-related policies. MethodsEvaluation was conducted against the pre-specified logic model for BIA-Obesity and established frameworks for analysing organisational change and corporate political activity. Outcomes evaluated included company engagement with the Initiative, level of media coverage, and impact of the Initiative on company policies and practices based on the perspectives of company representatives. A mixed methods design was employed, including surveys and in-depth interviews with company representatives, and media reports. ResultsApproximately half of invited companies participated in the evaluation of the BIA-Obesity Australia Initiative. A number of company representatives indicated that the Initiative had influenced their company's nutrition policies, strategies, and disclosure practices, and had raised their company's awareness of the importance of addressing nutrition issues. ConclusionCompany representatives perceive benchmarking and accountability initiatives as helpful for provoking improvements in nutrition-related policies and practices in their companies. However, the benefits of these initiatives need to be assessed in the context of the broader political and economic environment. Whilst the focus of accountability initiatives, such as BIA-Obesity, are on industry self-regulation efforts, they can also play an important role in drawing attention to the need for increased government regulation.